أسباب الهجرة غير القانونية للأفارقة وسبل مكافحتها - الوافي, عبد الرزاق; صحراوي, العيد (جامعة الوادي University of Eloued, 2020)
حاول الباحث من خلال هذه الدراسة للوصول إلى أهم الأسباب والدوافع المؤدية للهجرة غير القانونية للأفارقة نحو القارة الأوروبية و سبل مكافحتها، هذه الدوافع التي تتعلق بالإنسانية والحياة الكريمة للفرد الإفريقي والتي تؤثر بدورها في زيادة تعداد المهاجرين غير الشرعيين نحو الغرب وإلى الدول الأوربية خاصة التي تعتبر اللجوء غير الشرعي إلى مناطقها يزيد من وجود مشاكل اجتماعية واقتصادية وحتى سياسية. كما أن هناك دولا تعاني من الشيخوخة ونقص في اليد العاملة تعمل على تشجيع الهجرة إليها، وتوجد دول أخرى تعتبر الأفارقة مشكلة وتعمل على رفض استقبالهم، لكن إجمالا الجميع متفق في أوروبا وحتى في إفريقيا أن الهجرة غير القانونية هي مشكلة ومعضلة حقيقية لكل الأطراف. Through this study, the researchertried to reach the most important causes and motives leading to the illegal immigration of Africans to the European continent and ways to combat it, these motives related to humanity and a decent life for the Africanindividual, which in turn affects the increase in the number of illegal immigrants to the West and to European countries in particular that are considered illegalasylum to Its regionsincrease the presence of social, economic and evenpoliticalproblems. There are also countries that suffer from aging and a shortage of manpower working to encourage immigration to it, and there are other countries that consider Africans a problem and refuse to receive them, but in general everyone agrees in Europe and even in Africa that illegal immigration is a real problem and dilemma for all parties.
The causes of illegal immigration of Africans and ways to combat it
مقال
Keywords: Illegal immigration ; Poverty ; Wars ; Job Opportunities ; ways